Investigating the role of a Tannerella forsythia HtrA protease in host protein degradation and inflammatory response - Bloch, Susanne; Hager-Mair, Fiona F.; Bacher, Johanna; Tomek, Markus B.; Janesch, Bettina; Andrukhov, Oleh; Schäffer, Christina (Frontiers in Oral Health, 2024)
Introduction: Degradation of host proteins by bacterial proteases leads to the subversion of the host response and disruption of oral epithelial integrity, which is considered an essential factor in the progression of periodontitis. High-temperature requirement A (HtrA) protease, which is critical for bacterial survival and environmental adaptation, is found in several oral bacteria, including the periodontal pathogen Tannerella forsythia. This study investigated the proteolytic activity of HtrA from T. forsythia and its ability to modulate the host response.Methods: HtrA of T. forsythia was identified bioinformatically and produced as a recombinant protein.T. forsythia mutants with depleted and restored HtrA production were constructed. The effect of T. forsythia wild-type, mutants and recombinant HtrA on the degradation of casein and E-cadherin was tested in vitro. Additionally, the responses of human gingival fibroblasts and U937 macrophages to the different HtrA-stimuli was investigated and compared to those triggered by the HtrA-deficient mutant.Results: T. forsythia wild-type producing HtrA as well as the recombinant enzyme exhibited proteolytic activity towards casein and E-cadherin. No cytotoxic effect of either the wild-type, T. forsythia mutants or rHtrA on the viability of host cells was found. In hGFB and U937 macrophages, both T. forsythia species induced an inflammatory response of similar magnitude, as indicated by gene and protein expression of interleukin (IL)-1β, IL-6, IL-8, tumour necrosis factor α and monocyte chemoattractant protein (MCP)-1. Recombinant HtrA had no significant effect on the inflammatory response in hGFBs, whereas inn U937 macrophages, it induced a transient inflammatory response at the early stage of infection.HtrA of T. forsythia exhibit proteolytic activity towards the host adhesion molecule Ecadherin and has the potential to influence the host response. Its role in the progression of periodontitis needs further clarification.